Islamic Religious Education and Moral Education: The Foundation of Children's Character in the Age of Disruption - Mungafif, Mungafif (Global Education Journal, 2025)
This study aims to analyze the urgency of integrating Islamic Religious Education (PAI) and moral education in shaping the character of elementary school students in the disruptive era. This research employs a descriptive qualitative approach using the library research method, drawing upon textbooks, legislation, and scholarly articles as primary data sources. The analysis was conducted using content analysis techniques to identify the strategic role of PAI and moral education in building a solid foundation of character amidst globalization and rapid digital technology development. The findings indicate that PAI provides a strong theological and spiritual foundation, while moral education strengthens adaptive and ethical social behavior. The integration of both has become an urgent necessity in addressing the challenges of the disruptive era, such as exposure to negative digital content, shifting value authority, and declining face-to-face social interactions. Effective implementation strategies include contextual learning, teacher role modeling, habituation of positive behavior, and active involvement of parents and communities. This study recommends the development of a systematic and sustainable character education program based on PAI and moral education to nurture a generation that is faithful, knowledgeable, virtuous, and capable of adapting to global dynamics without losing their Islamic and Indonesian identity.